Status Epilepticus Type, Etiology, and Treatment: One-year Data - Didar Çolakoğlu; Humay İsmayilzade; Berk Büke; Kadriye Ağan; İpek Midi (Archives of Epilepsy, 2024)

(untitled)
Objective: This study aimed to review the demographic characteristics, type, and etiology of status epilepticus (SE) cases followed in our hospital for a period of 1 year and to reveal the factors affecting the prognosis of the patients. Methods: Patients diagnosed with SE among the patients who applied to the emergency department of our hospital within a 1-year period (August 2018 and August 2019) and who were consulted to us because of epileptic seizures or changes in consciousness and behavior while being followed up in the services or intensive care unit were retrospectively screened. Results: A total of 51 patients, 28 female (54.9%) and 23 male (45.1%), were included in our study. Twenty-eight patients were under or equal to the age of 60, and 23 patients were over the age of 60. Twenty-one patients had convulsive SE, 18 patients had non-convulsive SE (NCSE), and 14 patients were transitioning from convulsive SE to NCSE. Causes of SE were; lack of anti-seizure drugs (ASD) in 9 patients, intracranial mass in 9 patients, infection in 8 patients, and cerebrovascular event in 6 patients. Refractory SE cases were mostly observed in patients who developed SE due to lack of ASD and infection. In addition to first-line treatment with benzodiazepines, intravenous (IV) phenytoin, levetiracetam, valproic acid, and oral topiramate and lacosamide treatments were used. It was observed that 26 patients who developed refractory SE were treated with IV midazolam, propofol, or thiopental infusion. It was observed that 2 patients died because of refractory seizures. Conclusion: SE is an important condition that requires rapid treatment and can be fatal. In this cross-sectional study, the demographic characteristics and etiological causes of SE cases registered in our center were presented, and the characteristics of refractory SE cases were also mentioned.